ANALISIS PENINGKATAN FASILITAS KEAMANAN PEMUSTAKA DI PERPUSTAKAAN FAKULTAS KEDOKTERAN, KESEHATAN MASYARAKAT DAN KEPERAWATAN UNIVERSITAS GADJAH MADA DI ERA NEW NORMAL - Alfi Gladis Romadhona; Tafrikhuddin Tafrikhuddin (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Ilmu Budaya, UIN Sunan Kalijaga Yogyaka, 2021)
This study aims to find out how to improve the security facilities of the FK-KMK UGM Library in preparing the infrastructure for user security facilities in the new normal era and to find out how the security facilities used in the FK-KMK UGM library in ensuring the safety of users in the new normal era. This research is a type of qualitative descriptive research. Data collection techniques are observation, interviews and documentation. The data analysis technique used in this research is data reduction, data presentation and conclusion drawing. Based on this study, it was concluded that the level of user safety in the FK-KMK UGM library in the new normal era can be seen from the adaptation efforts made by the library, from online and offline services and the availability of security facilities in the form of handwashing facilities, temperature measurement sites and the availability of hand sanitisers at each room.